Relationship between acute kidney injury and brain MRI findings in asphyxiated newborns after therapeutic hypothermia - Sarkar, Subrata; Askenazi, David J; Jordan, Brian K; Bhagat, Indira; Bapuraj, J R; Dechert, Ronald E; Selewski, David T (Pediatric research, 2014)
We hypothesized that acute kidney injury (AKI) in asphyxiated neonates treated with therapeutic hypothermia would be associated with hypoxic-ischemic lesions on brain magnetic resonance imaging (MRI). Medical records of 88 cooled neonates who had had brain MRI were reviewed. All neonates had serum creatinine assessed before the start of cooling; at 24, 48, and 72 h through cooling; and then on day 5 or 7 of life. A neonatal modification of the Kidney Disease: Improving Global Outcomes guidelines was used to classify AKI. MRI images were evaluated by a neuroradiologist masked to outcomes. Outcome of interest was abnormal brain MRI at 7-10 d of life. AKI was found in 34 (39%) of 88 neonates, with 15, 7, and 12 fulfilling criteria for stages 1, 2, and 3, respectively. Brain MRI abnormalities related to hypoxia-ischemia were present in 50 (59%) newborns. Abnormal MRI was more frequent in infants from the AKI group (AKI: 25 of 34, 73% vs. no AKI: 25 of 54, 46%; P = 0.012; odds ratio (OR) = 3.2; 95% confidence interval (CI) = 1.3-8.2). Multivariate analysis identified AKI (OR = 2.9; 95% CI = 1.1-7.6) to be independently associated with the primary outcome. AKI is independently associated with the presence of hypoxic-ischemic lesions on postcooling brain MRI.